A fast, semi-analytical model for the Venusian binary cloud system. Issue 1 (5th July 2022) - Dai, L-K; Zhang, X; Cui, J
ABSTRACT: The Venusian clouds originate from the binary condensation of H2 SO4 and H2 O. The two components strongly interact with each other via chemistry and cloud formation. Previous works adopted sophisticated microphysical approaches to understand the clouds. Here, we show that the observed vapour and cloud distributions on Venus can be well explained by a semi-analytical model. Our model assumes local thermodynamical equilibrium for water vapour but not for sulphuric acid vapour, and includes the feedback of cloud condensation and acidity to vapour distributions. The model predicts strong supersaturation of the H2 SO4 vapour above 60 km, consistent with our recent cloud condensation model. The semi-analytical model is 100 times faster than the condensation model and 1000 times faster than the microphysical models. This allows us to quickly explore a large parameter space of the sulphuric acid gas-cloud system. We found that the cloud mass loading in the upper clouds has an opposite response of that in the lower clouds to the vapour mixing ratios in the lower atmosphere. The transport of water vapour influences the cloud acidity in all cloud layers, while the transport of sulphuric acid vapour only dominates in the lower clouds. This cloud model is fast enough to be coupled with the climate models and chemistry models to understand the cloudy atmospheres of Venus and Venus-like extra-solar planets.